Dielectric relaxation time behavior of B-site hybrid-doped BaTiO3ceramics - Thanapong Sareein (2018)
The time dependence of dielectric charge was investigated of Ba(Ti0.99-xMn0.01Tax)O3as a function of x = 0.0, 0.5, 0.1 and 1.5 mol% through the dependency of the dielectric permittivity on the frequency. A two part signal is considered as a behavior of aging in ferroelectrics: one is the low electric field and the other is the high electric field. Aging of dielectric has been calculated under the dielectric decay function which corresponds to observed de-polarization according to aging effect driven by charged defects with high activation energy. It was found that the aging behavior change significantly with donor dopant concentration. © 2014 Copyright Taylor and Francis Group, LLC.